2023
DOI: 10.1038/s41419-023-05987-7
|View full text |Cite
|
Sign up to set email alerts
|

SQLE promotes pancreatic cancer growth by attenuating ER stress and activating lipid rafts-regulated Src/PI3K/Akt signaling pathway

Abstract: Pancreatic cancer (PC), a highly lethal malignancy, commonly exhibits metabolic reprogramming that results in therapeutic vulnerabilities. Nevertheless, the mechanisms underlying the impacts of aberrant cholesterol metabolism on PC development and progression remain elusive. In this study, we found that squalene epoxidase (SQLE) is a crucial mediator of cholesterol metabolism in PC growth. We observed a profound upregulation of SQLE in PC tissues, and its high expression was correlated with poor patient outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 48 publications
2
13
0
Order By: Relevance
“…Additionally, it has been proposed that the molecular mechanism driving SQLE expression may involve p53 deletion or mutation [ 23 ]. SQLE also contributes to cholesterol-dependent lipid raft formation and promotes the activation of the Src-PI3K-Akt signaling pathway in pancreatic cancer [ 7 ]. In addition, SQLE plays a cancer-promoting role among other cancer types [ 19 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, it has been proposed that the molecular mechanism driving SQLE expression may involve p53 deletion or mutation [ 23 ]. SQLE also contributes to cholesterol-dependent lipid raft formation and promotes the activation of the Src-PI3K-Akt signaling pathway in pancreatic cancer [ 7 ]. In addition, SQLE plays a cancer-promoting role among other cancer types [ 19 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…TBF and NB-598, which are widely accessible SQLEi, have been shown to impede the growth and proliferation of HCC, pancreatic cancer and prostate cancer in both in vitro and in vivo studies [ 7 , 8 , 23 , 35 , 36 ]. Our research also confirmed the suppressive effect of TBF and NB-598 on LUSC proliferation and invasion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SQLE, as the second key enzyme in cholesterol biosynthesis, catalyzes the initial oxygenation step [ 20 ]. Squalene is converted by SQLE to (S)-2,3-epoxysqualene during cholesterol synthesis, but limited information is currently available regarding the significance of (S)-2,3-epoxysqualene in cancer research [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Squalene is converted by SQLE to (S)-2,3-epoxysqualene during cholesterol synthesis, but limited information is currently available regarding the significance of (S)-2,3-epoxysqualene in cancer research [ 21 , 22 ]. SQLE is overexpressed in several cancers and the high expression of SQLE is closely related to the poor prognosis of cancer patients, including CRC [ 20 , 23 ]. It is reported that the poor survival of CRC patients with high SQLE expression is due to its promotion of tumor cell proliferation.…”
Section: Introductionmentioning
confidence: 99%